KEPATUHAN PAJAK UMKM DI KABUPATEN KUDUS - Nita Andriyani Budiman (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
This study aims to examine how the influence of demographic factors, taxation system, tax avoidance factors, economic conditions, and the level of trust on MSMEs tax compliance in Kudus District. The tax compliance tested is formal tax compliance and material tax compliance. Sampling technique used in this study is purposive sampling with the number of respondents as much as 79. Methods of data collection using a questionnaire survey and using multiple regression analysis in analyzing data. The results of this study indicate that partially demography factor, taxation system, tax avoidance factor, economic condition, and level of trust have no effect on formal tax compliance, while demography factor and tax system have positive effect on material tax compliance.